2017
DOI: 10.1152/ajprenal.00561.2015
|View full text |Cite
|
Sign up to set email alerts
|

In situ lactate dehydrogenase activity: a novel renal cortical imaging biomarker of tubular injury?

Abstract: Renal ischemia-reperfusion injury is the state of which a tissue experiences injury after a phase of restrictive blood supply and recirculation. Ischemia-reperfusion injury (I/R-I) is a leading cause of acute kidney injury (AKI) in several disease states, including kidney transplantation, sepsis, and hypovolemic shock. The most common methods to evaluate AKI are creatinine clearance, plasma creatinine, blood urea nitrogen, or renal histology. However, currently, there are no precise methods to directly assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 40 publications
4
65
0
Order By: Relevance
“…Our finding of decreased HP 13 C Bic production following IRI is in agreement with a recent study by Nielsen et al, which reported lower HP 13 C Pyr conversion to Bic in a rat model of unilateral IRI with 60 min of ischemia followed by 24 h of reperfusion. However, the investigators in that study also showed a decrease in 13 C Pyr conversion to Lac in the kidneys subjected to IRI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of decreased HP 13 C Bic production following IRI is in agreement with a recent study by Nielsen et al, which reported lower HP 13 C Pyr conversion to Bic in a rat model of unilateral IRI with 60 min of ischemia followed by 24 h of reperfusion. However, the investigators in that study also showed a decrease in 13 C Pyr conversion to Lac in the kidneys subjected to IRI.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy between the findings is probably attributable to the time of assessment. The study by Nielsen et al was performed at 24 h following IRI when many renal tubules were probably necrotic, with attendant loss of cellular LDH and low Pyr conversion to Lac . Indeed, other murine studies have shown significantly depressed renal LDH levels 18–24 h following IRI as a result of LDH release from necrotic cells .…”
Section: Discussionmentioning
confidence: 99%
“…This signal enhancement allows real-time imaging of metabolic pathways using 13 C-labeled endogenous substrates15. We have recently demonstrated metabolic alterations in post-ischemic unilateral IRI rats following hyperpolarized [1- 13 C]pyruvate infusion16. Showing an upregulation of the anaerobic pathways, similarly to what has been demonstrated in diabetic kidney171819, albeit lower total turnover, most likely caused by necrosis.…”
mentioning
confidence: 58%
“…The rest of the arterial blood was spun for plasma purification in heparin‐coated tubes. Kidney tissue and urine were collected as previously described …”
Section: Methodsmentioning
confidence: 99%